Socio-economic development of Czechia at the micro-regional level - Šašek, Miloslav (Rozwój społeczno-ekonomiczny Czech w skali mikroregionów, 2017)
The research purpose of the present article was identification of regional differences in population development, and some socioeconomic characteristics at the micro-regional level, wherein the latter are the catchment districts of the municipalities with extended powers (hereinafter referred to as SO ORP). The method applied was the comparison of the population development, education structure, and unemployment in SO ORP, and monitoring of their correlation dependence. The analysis results show that there is rather strong correlation between the migration attractiveness of the microregions, their population growth, and transformation success behind which the growing share of the university graduates in the population and relatively very low unemployment rate are standing. The micro-regions at SO ORP level assist in distinguishing continuous territories with either positive or negative population and socioeconomic development.
Biblioteka Regionalisty, 2017, Nr 17, s. 105-118
Keywords: population development; micro-region; socioeconomic development; unemployment; education structures; rozwój populacji; mikroregion; rozwój społeczno-gospodarczy; bezrobocie; struktury edukacyjne